Multimodal interaction enhanced representation learning for video emotion recognition - Xia, Xiaohan; Zhao, Yong; Jiang, Dongmei (Frontiers in Neuroscience, 2022)
Video emotion recognition aims to infer human emotional states from the audio, visual, and text modalities. Previous approaches are centered around designing sophisticated fusion mechanisms, but usually ignore the fact that text contains global semantic information, while speech and face video show more fine-grained temporal dynamics of emotion. From the perspective of cognitive sciences, the process of emotion expression, either through facial expression or speech, is implicitly regulated by high-level semantics. Inspired by this fact, we propose a multimodal interaction enhanced representation learning framework for emotion recognition from face video, where a semantic enhancement module is first designed to guide the audio/visual encoder using the semantic information from text, then the multimodal bottleneck Transformer is adopted to further reinforce the audio and visual representations by modeling the cross-modal dynamic interactions between the two feature sequences. Experimental results on two benchmark emotion databases indicate the superiority of our proposed method. With the semantic enhanced audio and visual features, it outperforms the state-of-the-art models which fuse the features or decisions from the audio, visual and text modalities.